2000
DOI: 10.1253/jcj.64.641
|View full text |Cite
|
Sign up to set email alerts
|

Acute Inferior Myocardial Infarction and Coronary Spasm in a Patient With an Anomalous Origin of the Right Coronary Artery From the Left Sinus of Valsalva

Abstract: A 56-year-old Japanese woman with an acute inferior myocardial infarction was admitted to hospital. Emergency coronary angiography revealed an anomalous origin of the right coronary artery from the left sinus of Valsalva, but there was no stenosis or thrombus in either the right or left coronary artery. Coronary spasm was provoked at the site of the proximal portion of the anomalous coronary artery, which was located between the aorta and pulmonary trunk. This was thought to be the cause of the myocardial infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Myocardial ischemia in the inter-arterial variant can occur due to coronary spasm, intramural course of ARCOS within the aortic wall [2] or compression of the proximal segment due to aortic and pulmonary dilatation with increased cardiac output [5]. Narrow ostium of the aberrant artery with slit like orifice and acute angle take off is also known to compromise blood flow [6].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia in the inter-arterial variant can occur due to coronary spasm, intramural course of ARCOS within the aortic wall [2] or compression of the proximal segment due to aortic and pulmonary dilatation with increased cardiac output [5]. Narrow ostium of the aberrant artery with slit like orifice and acute angle take off is also known to compromise blood flow [6].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have also suggested that the oblique angle at the juncture of the anomalous RCA and the left coronary sinus might be a potential source because this creates a narrow orifice in the aortic wall that can collapse during exercise. [9] Moreover, Kaku et al [10] suggested that a spasm at the proximal portion of the RCA, which is situated between the aorta and the pulmonary artery, might also cause this condition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, percutaneous transluminal coronary angioplasty can also be carried out as an alternative to surgery, especially in cases involving MI. [13] Furthermore, in their study, Kaku et al [10] treated 56 middle-aged and elderly patients who had an anomalous origin of a coronary artery with beta-blockers, and although episodes of hypotension and arrhythmias were observed in 9% of the patients upon exertion, their five-year follow-up determined that the prognosis for those without atherosclerosis was relatively good, despite the lack of surgical treatment. Their results confirmed that none of the deaths were associated with the congenital anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…9 Zeppili et al 10 studied in vivo detection of coronary artery anomalies in asymptomatic 3150 athletes by echocardiographic screening and found two athletes (0,06%) with an RCA origin from the left sinus. Taylor et al 11 observed that, anomalous with the highest rate of sudden death with or without exercise (left or right coronary artery from the contralateral coronary sinus), 66% of patients were asymptomatic at the time of death.…”
Section: Discussionmentioning
confidence: 99%
“…King et al 12 reported that patients with anomalous origin of the RCA above the left SV had associated bicusbid aortic valve disease, while other authors did not observe this. 9 The length of high take-off of the RCA arising above the left SV in the range 1-4 cm. 1 Grollman et al 13 demonstrated systolic compression of the RCA arising from above the left sinus of Valsalva by aorta and pulmonary artery angiographically and postulated that the severity of the stenoses may be related to how far the ectopic origin is displaced toward the left and posteriorly, as well as the height of origin above the left SV.…”
Section: Discussionmentioning
confidence: 99%